Sensitivity of photoacoustic microscopy - Yao, Junjie (Elsevier, 2014)
Building on its high spatial resolution, deep penetration depth and excellent image contrast, 3D photoacoustic microscopy (PAM) has grown tremendously since its first publication in 2005. Integrating optical excitation and acoustic detection, PAM has broken through both the optical diffusion and optical diffraction limits. PAM has 100% relative sensitivity to optical absorption (i.e., a given percentage change in the optical absorption coefficient yields the same percentage change in the photoacoustic amplitude), and its ultimate detection sensitivity is limited only by thermal noise. Focusing on the engineering aspects of PAM, this Review discusses the detection sensitivity of PAM, compares the detection efficiency of different PAM designs, and summarizes the imaging performance of various endogenous and exogenous contrast agents. It then describes representative PAM applications with high detection sensitivity, and outlines paths to further improvement.